Achilles tendon stiffness is unchanged one hour after a marathon - Peltonen, J.; Cronin, N. J.; Stenroth, L.; Finni, T.; Avela, J. (The Journal of Experimental Biology, 2012)
Posited as one of the main adaptations that allowed early humans to adopt a terrestrial lifestyle, the Achilles tendon has played a significant role in our evolution. `It is one of the special characteristics in the human body that facilitate our endurance running and it may have assisted in the pursuit of prey`, says Jussi Peltonen and colleagues from the University of Jyväskylä, Finland. However, this critical tendon has an unfortunate tendency to rupture, leading many scientists to query why it is so vulnerable to damage when it has played such an essential role in our survival. Explaining that Achilles tendons rupture when they have lost stiffness, the Finnish team wondered whether long-distance endurance exercise might weaken the tendon, reducing its stiffness to make it increasingly vulnerable to damage (p. 3665).